Road to Tokyo Olympic Games: Do New Judo Rules Change the Technical-Tactical Behaviour of Elite Male Athletes? - Aedo-Munoz, E (Routledge, 2021)
This study compared the time-motion of the combat phases in male judo within two Olympic cycles (2016 vs. 2020). We analysed of 680 combats from belonging to two Olympic cycles (340 combats 2015–2016 and 340 combats 2019–2020). The combat phase was quantified according to a validated protocol (approach, gripping, attack/defence, groundwork, and pause). The 2020 cycle athletes spent less time in the gripping (79.7 ± 50.1 vs. 104.3 ± 54.1 seconds; p ˂ 0.001), attack/defence (7.6 ± 5.2 vs. 9.5 ± 7.2 seconds; p ˂ 0.001), and groundwork phases (33.9 ± 29.0 vs. 42.2 ± 32.0 seconds; p ˂ 0.001), and ashorter total combat time (200.0 ± 104.6 vs. 238.0 ± 94.8 seconds; p ˂ 0.001) than the 2016 athletes. Additionally, the 2020 athletes had ahigher occurrence of Golden Score (0.3 ± 0.4 vs. 0.1 ± 0.2 of total combats; p ˂ 0.001), and ahigher time spent in the Golden Score (23.9 ± 53.5 vs. 4.1 ± 21.4 seconds; p ˂ 0.001). The 2016 athletes had alonger total combat time; however, the time spent on the Golden Score increased in the 2020. These results should be helpful in preparing technical-tactical training aimed at performance. © 2021 Cardiff Metropolitan University.